Strategies for Enhancing Pakistan's Higher Education: Challenges, Opportunities, and Global Perspectives - Zohaib Hassan Sain; Mahadharu Ashifaati Ashfan; Ramil Abbasov; Nurulannisa Binti Abdullah; Uthman Shehu Lawal (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study uniquely examines Pakistan's higher education by integrating structural, institutional, and policy perspectives, emphasising global improvement strategies. Unlike prior studies focusing predominantly on barriers, this research innovatively identifies actionable opportunities for enhancing international competitiveness. A mixed methods approach was used to collect qualitative data through structured interviews and case studies from eight universities, including four public and four private. Quantitative data comprised surveys of 420 students, 20 faculty members, and four administrators, analysed using descriptive statistics and thematic content analysis. The three main challenges identified are inadequate funding and infrastructure, ineffective governance, and weak research culture. Conversely, the study highlights distinctive opportunities, including technology-enhanced learning platforms, international academic partnerships, and stronger industry-academia collaborations. Recommendations prioritise investing significantly in educational infrastructure, establishing robust quality assurance mechanisms, introducing affordable tuition policies, enhancing faculty professional development, improving governance transparency, expanding online learning initiatives, and actively pursuing global academic alliances. By explicitly linking specific challenges with strategic opportunities, this study provides novel, evidence-based directions for policymakers, administrators, and educators to improve Pakistan's higher education sustainably, strengthening its global competitiveness and overall academic excellence.